Temporomandibular joint imaging techniques [Temporomandibular eklem görüntüleme yöntemleri] - YILDIZ, COŞKUN; ŞANIVAR ABBASGHOLIZADEH, ZELİHA (Cumhuriyet University Faculty of Dentistry, 2015)
Invention of new techniques and improvement of especially computer systems were provided better assessment of TMJ anatomy and functions. Pathophysiology of TMD was better understood with images associated clinical findings. Understanding of TMD's improvements were caused emergence of new treatment approaches. TMJ imaging techniques can be arranged as direct radiographies, conventional tomography, panoramic radiography, kinetic X-ray imaging, arthrography, ultrasonography, computerized tomography, magnetic resonance imaging, nuclear medicine, cephalometric radiography. The technique is chosen which is best showing the pathology of hard and soft tissues, most easily accessible as equipment, the radiation dose of at least and most suitable for other contraindications. At this review, TMJ imaging techniques were summarized.
Keywords: Imaging techniques; TMJ